Kenya: ClimBeR Inception Workshop Report - Rose, Sabrina; Valencia, Lina; Schapendonk, Frans; Girvetz, Evan Hartunian (CGIAR System Organization, 2022)
The CGIAR Initiative on Climate Resilience, ClimBeR, aims to transform the climate adaptation capacity of food, land, and water systems in Kenya and five other countries, ultimately increasing the resilience of smallholder production systems to withstand severe climate change effects like drought, flooding, and high temperatures. The ClimBeR Initiative in collaboration with Kenya’s Ministries of Environment and Forestry and Agriculture, Livestock, Fisheries and Cooperatives, African Union Development Agency (AUDA-NEPAD), and the African Group of Negotiators Experts Support (AGNES) organized a workshop to bring stakeholders together to co-produce knowledge and innovations that could contribute to building systemic resilience against climate variability and extremes in Kenya. The main objective of this workshop was to develop a common vision and an action plan on how ClimBeR can support and strengthen climate adaptation efforts in Kenya. 41 national and regional organizations that have a presence in Kenya were represented in this meeting at the Fairmont The Norfolk Hotel. 75 participants attended in person and at least 5 participants joined online. The gender balance of the meeting was approximately 50 percent, and approximately 78 percent of attendees were based in Kenya. Please refer to Annex 1 for a detailed list of participants. ClimBeR aligns with key national and local priorities related to social equity (particularly with farmers in the arid and semi-arid lands), the climate security and agriculture nexus, coordination across ministries on climate and agricultural issues, and access to climate finance. This inception workshop demonstrated that there is significant momentum for climate resilience action in Kenya. ClimBeR is closely aligned with partner’s demands but there is more work to be done to ensure ClimBeR is Kenya’s initiative, where partners are leading the agenda.